Analysis of students’ mistakes in solving system of linear equation in three variables: A case on HOTS problems - Arik Hariati; Dimas Danar Septiadi (International Journal on Teaching and Learning Mathematics, 2019)
One of the serious mathematics problem faced by students happen when it relates to Higher Order Thinking Skills (HOTS) type which is compulsary of 2013 Curriculum. The purpose of this research is to describe the analysis of these types of students’ mistakes in solving mathematics problem of linear equation in three variables which used Higher Order Thinking Skills (HOTS) at SMAN Rambipuji Jember. The method used in this research is qualitative descriptive which describe the analysis' result on type of students mistakes based on Newman error indicator in terms of the students' cognitive level. The results showed that students with high cognitive level experiencing all kinds of errors with tendency to make a mistake on process error and  writing the final answer. While students with moderate cognitive level is experiencing four types of errors, they are errors to understand the problem, transform problem, process error, and writing the final answer. Students with low cognitive level experience three types of errors, they are transformation problem errors, process errors, and error in writing final answer with tendency to experiencing these three types of errors in problem completion.